Evolution and control of unethical practices in sales : a study of institutionalized bribery in developing country markets - Ameer, Irfan (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2019)
Bribery as an unethical sales practice is institutionalized in developing countries causing serious challenges for the smooth operations of multinational companies (MNCs). Therefore, their control is the primary concern for MNCs. Sales ethics and bribery in international business (IB) research largely focus on intra-organizational perspective. This perspective neglects the broader social context to understand and control bribery. Alternatively, institutional work in organization study is rich in investigating the social and dynamic nature of practices. However, this work ignores the invisible aspects of informal institutions, such as bribery. Against this background, the purpose of this research is to investigate the social and emergent nature of unethical practices in sales along with their control in developing country markets. The research builds on multiple theoretical perspectives: practice-based view (PBV); neo-institutional theory; and industrial network theory. The study employs a qualitative approach and the empirical data has been collected from the pharmaceutical industry in Pakistan since bribery practices in sales are widely prevailing in this market. This study achieves its goal via four articles. Research starts from a systematic review of existing knowledge in sales ethics. The review in article 1 reveals the need to study unethical behavior from a social practice perspective. As a result, article 1 introduces a PBV and its applications in sales ethics. The second article empirically examines the evolution process of bribery in sales. Findings show that bribery practices socially evolve in a sequential and partly overlapping process of four identifiable stages: early development; chain reaction; legitimization; and revision. The third and the fourth article included in this study emphasize on controlling bribery. The third article is conceptual that introduces a practice-based strategic framework for MNCs to control bribery in developing countries. Finally, the fourth article empirically investigates the nature of invisible pressure of institutionalized bribery and related practices of MNCs to respond. Findings related to the pressure indicate that MNCs closely monitor bribery practices of market actors to make sense of invisible pressure. Results further discover a range of MNCs practices to respond towards such pressure along with practices’ types, focus, objectives and intended actors. Overall this dissertation shifts the focus of sales ethics and bribery in IB research from the dominated intra-organizational view to PBV that helps to understand the social and dynamic nature of corrupt practices and their control. Study open new avenues for institutional work to understand the nature of invisible pressure arising from informal institutions and related organizational responses. Study further offers important implications for organizations and policymakers to understand and control practically significant bribery phenomenon in sales.

Myynnin yhteydessä tapahtuva lahjonta on usein laajasti institutionalisoitunut epäeettinen käytäntö, joka aiheuttaa vakavia haasteita monikansallisten yritysten toiminnalle kehitysmaiden markkinoilla. Myynnin etiikan ja kansainvälisen liiketoiminnan lahjontaa koskevat tutkimustraditiot korostavat organisaation sisäistä näkökulmaa lahjonnan kontrolloimiseen ja jättävät samalla laajemman sosiaalisen kontekstin huomioimatta. Organisaatiotutkimuksen institutionaalinen näkökulma puolestaan tutkii epäeettisten myyntikäytäntöjen sosiaalista ja dynaamista luonnetta, mutta keskittyy pääosin virallisiin instituutioihin. Epäviralliset ja näkymättömät instituutiot, kuten lahjonta, ovat saaneet vain vähän tutkijoiden huomiota osakseen. Näin ollen tämän väitöskirjan tarkoituksena on tutkia epäeettisten myyntikäytäntöjen sosiaalista luonnetta ja niiden kehittymistä ja kontrollointia kehitysmaiden markkinoilla. Tutkimusnäkökulma perustuu sosiaaliseen konstruktivismiin ja väitöskirjan teoreettinen viitekehys rakentuu kolmen teoreettisen näkökulman varaan: käytäntöpohjaiseen näkökulmaan, uusinstitutionaaliseen näkökulmaan ja teollisten verkostojen teoriaan. Tutkimuksen empiirisenä kontekstina on Pakistanin lääketeollisuudessa vallitsevat lahjontakäytännöt, joita tutkitaan laadullisilla menetelmillä. Väitöskirjatutkimus koostuu neljästä artikkelista. Ensimmäisessä artikkelissa tehdään systemaattinen kirjallisuuskatsaus myynnin etiikan tutkimukseen ja osoitetaan tarve tutkia epäeettistä käyttäytymistä sosiaalisena ja dynaamisena ilmiönä. Artikkeli esittelee käytäntöpohjaisen näkökulman nykytutkimuksen laajentamiseksi. Väitöskirjan toinen artikkeli tarkastelee lahjontakäytäntöjen kehittymistä pitkittäisten sosiaalisten tapahtumasarjojen pohjalta, ja tulokset paljastavat neljä vaihetta lahjontakäytäntöjen muodostumisessa: aikainen kehitys, ketjureaktio, laillistuminen ja uudistuminen. Artikkeli lisää ymmärrystä lahjontakäytäntöjen sosiaalisesta ja dynaamisesta luonteesta. Tutkimuksen kolmas ja neljäs artikkeli keskittyvät lahjontakäytäntöjen kontrollointiin. Kolmas artikkeli on käsitteellinen ja rakentaa käytäntöpohjaisen viitekehyksen monikansallisille yrityksille institutionalisoituneen lahjonnankontrolloimiseksi kehitysmaiden markkinoilla. Viimeinen, neljäs artikkeli perustuu jälleen empiiriseen materiaaliin ja keskittyy tarkastelemaan institutionalisoituneiden lahjontakäytäntöjen luomaa painetta yrityksille sekä monikansallisten yritysten reagointimalleja tähän paineeseen. Tulokset osoittavat, että monikansalliset yritykset seuraavat tarkasti markkinatoimijoiden lahjontakäytäntöjä ja että niillä on käytössään useita eri strategioita ja niihin kytkeytyviä toimintatapoja, joilla ne pyrkivät vastaamaan syvälle juurtuneeseen lahjontaan. Väitöskirja laajentaa myyntietiikan ja kansainvälisen liiketoiminnan lahjontatutkimusta hallitsevista organisaation sisäisistä näkökulmista kohti käytäntöpohjaista näkökulmaa. Tämä näkökulma auttaa korruptiokäytäntöjen monimutkaisen sosiaalisen ja dynaamisen luonteen ymmärtämisessä sekä lahjonnan kontrolloimisessa ja avaa uusia väyliä institutionaaliselle tutkimukselle epävirallisten instituutioiden ymmärtämiseksi ja hallitsemiseksi. Käytäntönäkö-kulmasta tuotetut tulokset tarjoavat myös organisaatioille ja päättäjille konkreettisia keinoja vastata lahjonnan monisyiseen ongelmaan.